Perancangan sistem informasi pengelolaan kendaraan dinas berbasis web di PT Shoetown Kasokandel Indonesia - Junior, Fabio (Universitas Tangerang Raya, 2022)
Business travel is one of the most important activities at PT Shoetown Kasokandel Indonesia which aims to carry out a certain task or so that vehicle management will be needed when you want to go on a business trip. In carrying out the business process, the proposer, logistics, finance and superiors face problems in terms of managing vehicles for official travel, namely the process of proposing and granting permits is less practical, for example the vehicle proposer has to meet the logistics officer, and the logistics officer meets the superiors and finances of PT Shoetown Kasokandel Indonesia in managing vehicle demand. Therefore, the online-based vehicle management application for business trips has information management features for proposing vehicle request letters for business trips and vehicle maintenance management. This application was created using the waterfall method with the UML model using the PHP programming language and using MySQL as the database server. Users of this application are employees of PT Shoetown Kasokandel Indonesia, including staff, logistics, finance, superiors.